PENGARUH PEMBERIAN KONSELING DENGAN MEDIA VIDEO TERHADAP PENGETAHUAN IBU TENTANG BIRTH BALL PADA PROSES PERSALINAN - Veradilla; Faulia Mauluddina; Novia Amerti Dwi Puspita Sari (LPPM STIKes Mitra Adiguna, 2024)
Normal delivery is the process of expelling (birth) products of conception that can live outside the uterus through the vagina to the outside world. This process can be said to be normal or spontaneous if the baby is born in the back of the head position without the help of tools or assistance, and does not injure the mother and baby. In general, this process takes place in less than 24 hours. The aim of the research is to determine the effect of providing counseling using video media on mothers' knowledge about birth balls during the birthing process. This research is quantitative research, with a pre-experimental research design. Using the one group pretest-posttest design method, namely a research design that includes a pretest before treatment and a posttest after treatment. In this way, it can be known more accurately, because it can be compared with what was done before the treatment was given. The sample in this study was all pregnant women in the third trimester, totaling 44 respondents at the Image Clinic. From the research results of the discussion above, the researcher concluded that there was an influence of providing counseling using video media on mothers' knowledge about birth balls during the birthing process. that video media can make it easier for respondents to increase mothers' knowledge about birth ball. Video media is more recommended in providing education because the absorption of information is more effective by using the sense of sight in the form of images which are more interesting than the sense of sight which is only in the form of writing, and is not boring because it is pictorial. lively and easy to understand. Respondents are more interested in watching videos via cellphone, so that the respondent's behavior improves.